KAJIAN KESESUAIAN PENATAAN RUANG TERBUKA PUBLIK DI KAWASAN PASAR ACEH KOTA BANDA ACEH DENGAN KOMPONEN DAN INDIKATOR PERANCANGAN TAMAN KOTA SERTA RTRW KOTA BANDA ACEH 2009-2029 - Nora Damayanty; Izziah Izziah; Renni Anggraini (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
The public open space in the city center is the identity of a city, which is a gathering place for the community for conducting activities, trading, celebrating, or just spending their spare time. Banda Aceh government has launched Aceh market area as one of historic area (heritage) as well as strategic area of Banda Aceh city. The purpose of this study is to identify factors that led to the transition of function and suitability of the arrangement of public open space facilities through Jhon Lang's theory of Urban Park Design Indicators and RTRW Banda Aceh City 2009-2029. The research methodology used is mixed methods with descriptive analysis. The result of the research shows that the arrangement of public open space facility in Pasar Aceh area has not been in accordance with Urban Design Indicator and RTRW Banda Aceh City 2009-2029. Those become the factor causing the shift of public open space function in Aceh market area. The lack of strict rules governing the parking of vehicles and street vendors also become factors causing the transition of public open space functions in the Aceh market area. Data obtained from the results of the study were analyzed by using SWOT. The SWOT analysis where obtained thre alternative strategy could be applied  are : implementation of rules on arrangement and utilization of public open space in the Aceh Market area to be well ordered; implementation of rules with clear law enforcement will discipline street hawkers and motor vehicle owners who abuse public open space function in Aceh Market area;  providing public open space supporting facilities and infrastructure in Aceh Market area in accordance with the theory of Urban Park Design Components and Indicators, RTRW Banda Aceh City 2009-2029.